Abordagens para o ensino e aprendizagem de algoritmos ou equivalente com base em elementos de jogos: um estudo a partir do mapeamento sistemático da literatura - MENEZES, Julio de Pádua Lopes (2019)
The use of element-based approaches (methods, techniques, tools, among others) that help the algorithm and related education, despite recent has been gaining prominence in academic publications. This is because the use of these approaches can contribute to increasing the involvement and engagement of students in basic disciplines of information technology (it). The aim of this study is to investigate, from a Systematic Mapping of literature (MSL), the main game elements-based approaches that have been used as support for the teaching and learning process and introduction to algorithm programming, in the context of upper-level courses in the it field. In other words, build a mapping of the main trends of researches developed involving approaches based on elements of games geared to teaching algorithm and programming, with the aim of validating the results through scientific evidence. A study from the Systematic Mapping of the literature to identify primary studies focusing on teaching algorithm and programming. 10,027 primary studies were identified, published between 2006 and 2016. Preliminary studies show a growing concern in developing experiences from approaches based on elements of games distributed by 23 countries in several continents by the world because in 61 articles selected were identified approaches based on elements of games, be they, by the use of serious games, game elements and of gamification.